2007
DOI: 10.1002/dys.340
|View full text |Cite
|
Sign up to set email alerts
|

Unimpaired implicit learning in children with developmental dyslexia

Abstract: Children with dyslexia have consistently been found to have a variety of deficits in motor, cognitive, and sensory processes; however, the few studies that have been reported of the implicit learning ability of these children have produced conflicting results. The present study aimed to investigate the implicit learning abilities of children with developmental dyslexia using a simple cued reaction time task which has not been studied with this group previously. Twenty-three children with developmental dyslexia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
28
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 25 publications
0
28
2
Order By: Relevance
“…mirror drawing), found a diminished performance of children with developmental dyslexia. On the contrary, Roodenrys and Dunn (2007) using a simple SRTT found intact implicit learning performance in children with developmental dyslexia. Taken together the studies suggest that implicit learning abilities are found impaired in children with developmental dyslexia when (1) explicit learning abilities are intact (Vicari et al, 2003) and (2) when the complexity of the learning environment is increased (Vicari et al, 2005) irrespective of the learning materials (Folia et al, 2008).…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…mirror drawing), found a diminished performance of children with developmental dyslexia. On the contrary, Roodenrys and Dunn (2007) using a simple SRTT found intact implicit learning performance in children with developmental dyslexia. Taken together the studies suggest that implicit learning abilities are found impaired in children with developmental dyslexia when (1) explicit learning abilities are intact (Vicari et al, 2003) and (2) when the complexity of the learning environment is increased (Vicari et al, 2005) irrespective of the learning materials (Folia et al, 2008).…”
mentioning
confidence: 78%
“…Overall, the studies provide evidence that while some implicit learning abilities remain robust (Roodenrys & Dunn, 2007) in children with developmental dyslexia, others are affected (Vicari et al, 2003(Vicari et al, , 2005. More specifically, Vicari et al (2003) found impaired implicit sequence learning in school-aged children with developmental dyslexia despite intact explicit learning abilities.…”
mentioning
confidence: 88%
See 3 more Smart Citations